Virtual reality and psychedelics: new perspectives and new possibilities in the treatment of alcohol use disorder - Matthews, Scott; Greco, Antonino; Rastelli, Clara; Bassir Nia, Anahita (Frontiers in Psychiatry, 2025)
Psychedelic-assisted therapy is a remarkably promising treatment for substance use disorders and for alcohol use disorder (AUD) in particular. Research supporting psychedelics as a safe and effective pharmacotherapy for AUD and its comorbid psychiatric conditions dates from the late1940s and includes over 2,000 published studies. There are, however, challenges to the clinical implementation of psychedelics on a scale appropriate to a highly prevalent disease. Virtual reality applications can aid in meeting these challenges. Studies have shown that virtual reality simulations of psychedelic phenomenology (VRP) can replicate neurophysiological and behavioral markers of classic serotonergic psychedelics when viewed by healthy subjects. The results of these studies suggest VRP may have utility as an adjunct to or replacement for aspects of psychedelic-assisted therapy. Here, we introduce four potential clinical applications for VRP in psychedelic-assisted therapy: to prepare for psychedelics, to extend and enhance their efficacy, to facilitate integration following psychedelic dosing, and to standardize the set and setting. VRP may also have application to clinical research in psychedelics as a placebo and as a tool for interrogating the subjective experience of psychedelics in the therapeutic setting. Integrating virtual reality into psychedelic therapy and research holds the promise of new possibilities for psychedelic treatment and new pathways to their implementation.